Daylighting the Environmental Social Sciences for Coastal Management: Introduction to the Special Issue - Sara Jo Breslow; Rebecca Hollender; David J. Trimbach; Tomas M. Koontz; Michael H. Chang; Robert M. Anderson; Mary Ann Rozance; Julie Watson; Kyle Clifton; Maura Flight; Robby Fonner; Connor Lewis-Smith; et al. (Coastal Management, 2026)

The genetic landscape of Pacific taro: diversity, population structure, and strategic germplasm management - Caroline M. Mitchell; Amit Sukal; Anastasija Podolyan; Sera Dau; Renuma Kumar; Semi Cakaunitavuki; Preeti Nand; Connor Watson; Logotonu M. Waqainabete; Gary J. Houliston (Genetic Resources and Crop Evolution, 2026)

Preserving tororaro’s legacy: conservation genetics of in-situ and ex-situ populations of Muehlenbeckia astonii (Polygonaceae) - Caroline M. Mitchell; Connor Watson; Peter B. Heenan (New Zealand Journal of Botany, 2025)

Fish consumption advice is depriving children of neurolipids and other nutrients essential to brain and eye development - Philip Spiller; J. Thomas Brenna; Susan E. Carlson; Jean Golding; Michael A. Crawford; Joseph R. Hibbeln; Berthold V. Koletzko; John Columbo; Penny Kris-Etherton; Sonja L. Connor; Clark Carrington; P. Michael Bolger; et al. (NeuroToxicology, 2025)

Embracing social-ecological system complexity to promote climate-ready fisheries - Chris J. Harvey; Patricia M. Clay; Rebecca Selden; Stephanie K. Moore; Kelly S. Andrews; Yvonne L. deReynier; Anne H. Beaudreau; Owen R. Liu; Karma C. Norman; Jameal F. Samhouri; Lyall Bellquist; Merrick Burden; et al. (Reviews in Fish Biology and Fisheries, 2025)

Impact of locational pricing on the roll out of heat pumps in the UK - Andrew Lyden; Samuel Alene; Peter Connor; Renaldi Renaldi; Stephen Watson (Energy Policy, 2024)

Venous Thromboembolism: Review of Clinical Challenges, Biology, Assessment, Treatment, and Modeling - Connor Watson; Hicham Saaid; Vijay Vedula; Jessica C. Cardenas; Peter K. Henke; Franck Nicoud; Xiao Yun Xu; Beverley J. Hunt; Keefe B. Manning (Annals of Biomedical Engineering, 2024)

Correction to: Inflammasome‑Regulated Pyroptotic Cell Death in Disruption of the Gut‑Brain Axis After Stroke - Nadine A. Kerr; Juliana Sanchez; Gregory O’Connor; Brant D. Watson; Sylvia Daunert; Helen M. Bramlett; W. Dalton Dietrich (Translational Stroke Research, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Performance of a Hydrogel Coated Nitinol with Oligonucleotide-Modified Nanoparticles Within Turbulent Conditions of Blood-Contacting Devices - Connor Watson; Lidya Abune; Hicham Saaid; Connie Wen; Yong Wang; Keefe B. Manning (Cardiovascular Engineering and Technology, 2023)

Inflammasome-Regulated Pyroptotic Cell Death in Disruption of the Gut-Brain Axis After Stroke - Nadine A. Kerr; Juliana Sanchez; Gregory O’Connor; Brant D. Watson; Sylvia Daunert; Helen M. Bramlett; W. Dalton Dietrich (Translational Stroke Research, 2022)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Decreased activation of placental mTOR family members is associated with the induction of intrauterine growth restriction by secondhand smoke in the mouse - Camilo Mejia; Josh Lewis; Clinton Jordan; Juan Mejia; Connor Ogden; Troy Monson; Duane Winden; Marc Watson; Paul R. Reynolds; Juan A. Arroyo (Cell and Tissue Research, 2017)

Facilitating adaptation of biodiversity to climate change: a conceptual framework applied to the world’s largest Mediterranean-climate woodland - Suzanne M. Prober; Kevin R. Thiele; Philip W. Rundel; Colin J. Yates; Sandra L. Berry; Margaret Byrne; Les Christidis; Carl R. Gosper; Pauline F. Grierson; Kristina Lemson; Tom Lyons; Craig Macfarlane; et al. (Climatic Change, 2012)

API Quality by Design Example from the Torcetrapib Manufacturing Process - Dave am Ende; Karen S. Bronk; Jason Mustakis; Gary O’Connor; Charles L. Santa Maria; Roger Nosal; Timothy J. N. Watson (Journal of Pharmaceutical Innovation, 2007)

Decline in Relative Abundance of Bottlenose Dolphins Exposed to Long‐Term Disturbance - LARS BEJDER; AMY SAMUELS; HAL WHITEHEAD; NICK GALES; JANET MANN; RICHARD CONNOR; MIKE HEITHAUS; JANA WATSON‐CAPPS; CINDY FLAHERTY; MICHAEL KRÜTZEN (Conservation Biology, 2006)
Studies evaluating effects of human activity on wildlife typically emphasize short‐term behavioral responses from which it is difficult to infer biological significance or formulate plans to mitigate harmful impacts. Based on decades of detailed behavioral records, we evaluated long‐term impacts of vessel activity on bottlenose dolphins ( Tursiops sp.) in Shark Bay, Australia. We compared dolphin abundance within adjacent 36‐km 2 tourism and control sites, over three consecutive 4.5‐year periods wherein research activity was relatively constant but tourism levels increased from zero, to one, to two dolphin‐watching operators. A nonlinear logistic model demonstrated that there was no difference in dolphin abundance between periods with no tourism and periods in which one operator offered tours. As the number of tour operators increased to two, there was a significant average decline in dolphin abundance (14.9%; 95% CI =−20.8 to −8.23), approximating a decline of one per seven individuals. Concurrently, within the control site, the average increase in dolphin abundance was not significant (8.5%; 95% CI =−4.0 to +16.7). Given the substantially greater presence and proximity of tour vessels to dolphins relative to research vessels, tour‐vessel activity contributed more to declining dolphin numbers within the tourism site than research vessels. Although this trend may not jeopardize the large, genetically diverse dolphin population of Shark Bay, the decline is unlikely to be sustainable for local dolphin tourism. A similar decline would be devastating for small, closed, resident, or endangered cetacean populations. The substantial effect of tour vessels on dolphin abundance in a region of low‐level tourism calls into question the presumption that dolphin‐watching tourism is benign.

Novel titanocene anti-cancer drugs and their effect on apoptosis and the apoptotic pathway in prostate cancer cells - K. O'Connor; C. Gill; M. Tacke; F.-J. K. Rehmann; K. Strohfeldt; N. Sweeney; J. M. Fitzpatrick; R. W. G. Watson (Apoptosis, 2006)